Genome-wide siRNA Screen Identifies the Radiosensitizing Effect of Downregulation of MASTL and FOXM1 in NSCLC - Nagel, Remco; Stigter-van Walsum, Marijke; Buijze, Marijke; van den Berg, Jaap; van der Meulen, Ida H; Hodzic, Jasmina; Piersma, Sander R; Pham, Thang V; Jiménez, Connie R; van Beusechem, Victor W; Brakenhoff, Ruud H (Molecular cancer therapeutics, 2015)
Lung cancer is the most common cancer worldwide and on top of that has a very poor prognosis, which is reflected by a 5-year survival rate of 5% to 15%. Radiotherapy is an integral part of most treatment regimens for this type of tumor, often combined with radiosensitizing cytotoxic drugs. In this study, we identified many genes that could potentially be exploited for targeted radiosensitization using a genome-wide siRNA screen in non-small cell lung cancer (NSCLC) cells. The screen identified 433 siRNAs that potentially sensitize lung cancer cells to radiation. Validation experiments showed that knockdown of expression of Forkhead box M1 (FOXM1) or microtubule-associated serine/threonine kinase-like (MASTL) indeed causes radiosensitization in a panel of NSCLC cells. Strikingly, this effect was not observed in primary human fibroblasts, suggesting that the observed radiosensitization is specific for cancer cells. Phosphoproteomics analyses with and without irradiation showed that a number of cell-cycle-related proteins were significantly less phosphorylated after MASTL knockdown in comparison to the control, while there were no changes in the levels of phosphorylation of DNA damage response proteins. Subsequent analyses showed that MASTL knockdown cells respond differently to radiation, with a significantly shortened G2-M phase arrest and defects in cytokinesis, which are followed by a cell-cycle arrest. In summary, we have identified many potential therapeutic targets that could be used for radiosensitization of NSCLC cells, with MASTL being a very promising and druggable target to combine with radiotherapy.